2019
DOI: 10.1016/j.heliyon.2019.e02522
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alloying elements on the properties of pressed and non-pressed biodegradable Fe–Mn–Ag powder metallurgy alloys

Abstract: Current trends in the biodegradable scaffold industry call for powder metallurgy methods in which compression cannot be applied due to the nature of the scaffold template itself and the need to retain the shape of an underlying template throughout the fabrication process. Iron alloys have been shown to be good candidates for biomedical applications where load support is required. Fe–Mn alloys were researched extensively for this purpose. Current research shows that all metallurgical characterisation and corros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…A previous study focusing on the electrochemical behavior of Fe–Mn–C–Ag alloys already showed that such lean alloying did not produce any effect on the electrochemistry of these steels, leading even to a reduced corrosion current density . A similar trend in the mass loss was already observed in the literature for tests up to 28 days in a similar solution, while other researchers observed that the presence of Ag reduced the corrosion resistance of TWIP steels from electrochemical tests. , After 3 days, SEM analyses (Figure ) showed that some voids appeared around Ag particles, indicating that galvanic coupling could effectively take place, as the difference in electrochemical potential between Ag and TWIP steels could suggest. The galvanic coupling effect could explain why more nuclei of DPs were observed at the surface at 7 days with respect to the 0Ag alloy.…”
Section: Discussionsupporting
confidence: 75%
“…A previous study focusing on the electrochemical behavior of Fe–Mn–C–Ag alloys already showed that such lean alloying did not produce any effect on the electrochemistry of these steels, leading even to a reduced corrosion current density . A similar trend in the mass loss was already observed in the literature for tests up to 28 days in a similar solution, while other researchers observed that the presence of Ag reduced the corrosion resistance of TWIP steels from electrochemical tests. , After 3 days, SEM analyses (Figure ) showed that some voids appeared around Ag particles, indicating that galvanic coupling could effectively take place, as the difference in electrochemical potential between Ag and TWIP steels could suggest. The galvanic coupling effect could explain why more nuclei of DPs were observed at the surface at 7 days with respect to the 0Ag alloy.…”
Section: Discussionsupporting
confidence: 75%
“…Figure 7 gave strong evidence that the enhanced corrosion rate in the Fe‐35Mn‐1Ag is caused by the prevalence of microgalvanic corrosion, consistent with previous studies. [ 50,51,79 ] The areas around the Ag particles were all hollowed out, which indicates an advanced stage of corrosion of the Fe matrix. Niendorf et al.…”
Section: Discussionmentioning
confidence: 99%
“…Caligari Conti et al. [ 51 ] likewise reported that a 2% addition of Ag resulted in a five‐fold increase in in vitro degradation rate in fully austenitized Fe‐30Mn. Sotoudehbagha et al.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental difference in powder-processing microstructures and microstructures prepared using melt processing, is the resultant porosity in the former. To this effect, multiple groups have confirmed the increase in degradation resulting from increased percentage porosity in the tested samples [ 23 , 36 , 37 ]. Apart from this, powder-processed metal, especially FeMn-based alloys of interest in the field, are more susceptible to the formation of manganese oxide inclusions resulting from high temperature oxidation [ 38 ].…”
Section: Introductionmentioning
confidence: 90%